Kentrung Solokuro sebagai Representasi Toponimi Desa-Desa di Wilayah Pesisir Kabupaten Lamongan - Dewi Herlina; Sueb Sueb (Badan Pengembangan dan Pembinaan Bahasa, 2024)
This study aims to describe the toponymy of villages in the coastal area of Lamongan Regency. The researcher used the oral speech of Solokuro kentrung art as data to explore toponyms. In this study, the forms of linguistic units and categories of toponymy meaning of villages in the coastal area of Lamongan Regency will be identified. This study uses a qualitative descriptive method with a linguistic anthropological approach. The data in this study are the utterances of the mastermind behind the kentrung Solokuro, namely Mr. Ahmad Kusairi. The source of the data comes from a video of the Kentrung Solokuro art performance which was uploaded on the YouTube site entitled “Stories of Pesisir Lamongan 1”. The spoken data in the video is transcribed into written data and presented in the form of words based on the results of the researcher's interpretation of the observed behavior. Based on the results of the study, the names of the villages in the coastal area of Lamongan Regency are dominantly using polymorphemic words and based on their meanings are dominantly using aspects of cultural toponymy in the form of folklore. Efforts to document kentrung art need to be made to capture cultural and linguistic landscapes that future generations can benefit from. The results of this study are expected to provide an overview of the artistic values of Kentrung Solokuro from a linguistic point of view. AbstrakPenelitian ini bertujuan untuk mendeskripsikan toponimi desa-desa di wilayah pesisir Kabupaten Lamongan. Peneliti memanfaatkan tuturan lisan kesenian kentrung Solokuro sebagai data guna menelusuri toponim. Dalam penelitian ini, akan diidentifikasi bentuk satuan kebahasaan dan kategori makna toponimi desa-desa di wilayah pesisir Kabupaten Lamongan. Penelitian ini menggunakan metode deskriptif kualitatif dengan pendekatan antropologi linguistik. Data dalam penelitian ini adalah tuturan dalang kentrung Solokuro yaitu bapak Ahmad Kusairi. Sumber data berasal dari video pertunjukan kesenian Kentrung Solokuro yang diunggah di situs youtube berjudul “Cerita Pesisir Lamongan 1”. Data lisan pada video tersebut ditranskripsi ke data tulis dan disajikan dalam bentuk kata-kata berdasarkan hasil interpretasi peneliti terhadap perilaku yang diamati. Berdasarkan hasil penelitian, nama desa-desa di wilayah pesisir Kabupaten Lamongan dominan menggunakan kata polimorfemis dan berdasarkan maknanya dominan menggunakan aspek toponimi kebudayaan berupa folklor. Upaya pendokumentasian kesenian kentrung perlu diupayakan untuk memotret lanskap kebudayaan dan kebahasaan yang dapat dimanfaatkan generasi mendatang. Hasil kajian ini diharapkan dapat memberikan gambaran mengenai nilai-nilai kesenian Kentrung Solokuro dari sudut pandang linguistik.